Thermal conductivity and dynamic viscosity of mono and hybrid organic- and synthetic-based nanofluids: A critical review - At-Tasneem, Mohd Amin; Wan Azmi, Wan Hamzah; Oumer, Ahmed Nurye (De Gruyter, 2021)
Thermal conductivity and dynamic viscosity are two critical properties of nanofluids that indicate their heat transfer performance and flow. Nanofluids are prepared by dispersing mono or several organic or synthetic nanoparticles in selected base fluids to form mono or hybrid nanofluids. The qualitative and quantitative stability measurement of nanofluids will then be addressed, followed by a detailed discussion on how the dispersion of nanoparticles in water (W), ethylene glycol (EG), and themixture of W:EG 60:40%by volume affects the thermal conductivity and dynamic viscosity ratio. The data comparison demonstrated that the thermal conductivity ratio increases with increasing normalized concentrations, the bulk temperature of nanofluids, and the smaller nanoparticle size. The dynamic viscosity ratio is multiplied by the normalized concentration increase. Nevertheless, as the bulk temperature climbed from 0 to 80°C, the dynamic viscosity ratio was scattered, and the dynamic viscosity ratio trend dropped with increasing particle size. While the majority of nanofluids enhanced thermal conductivity ratio by 20%, adding carbon-based nanoparticles to synthetic nanofluid increased it by less than 10%. The disadvantage of nanofluids is that they multiply the dynamic viscosity ratio of all nanofluids, which increase power consumption and reduces the efficiency of any mechanical system.